Agaricus subrufescens: substratum nitrogen concentration and mycelial extraction method on antitumor activity - MÍRIA B.D. BERTÉLI (Anais da Academia Brasileira de Ciências)
ABSTRACT Antitumor activity of Agaricus subrufescens has been shown on vegetative mycelium and basidiocarp. However, few studies have assessed the effect of A. subrufescens cultivation conditions and extraction methods on antitumor activity. This study evaluated the effect of nitrogen concentration on the cultivation medium of A. subrufescens and the extraction method of mycelial antineoplastic actives against sarcoma 180 cells implanted in mice. Two nitrogen sources (isolated soybean protein and NaNO3) and 10 nitrogen concentrations (0.25 to 8.0 g/L) were used. Dried mycelium extract was obtained by hot water infusion (1:10 mass:volume; 90 °C) or by aqueous mixture (1:10 mass:volume, ambient temperature) in ultrapure water. The doses were administered daily by gavage to mice implanted with sarcoma 180 cells. Isolated soy protein is more efficient to mycelial biomass production than NaNO3. The mycelial biomass production increases when the cultivation medium is added with high nitrogen concentrations as well as the splenic index and the antitumor activity of the moistened mycelial powder. Hot water extract is more effective than the moistened mycelial powder to reduce tumor. The antitumor activity of hot water mycelial extract is similar to the one of basidiocarps, presenting lower metabolic demand on the spleen, keeping blood parameters normal and promoting animal wellness.